Relationship Of Patient Characteristics With Compliance With Lifestyle Modifications In Recovery Post Diabetes Mellitus Patients - Isnayati; Ricky Rianto Ikhsan; Sri Atun Wahyuningsih (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2020)
Diabetes mellitus is a group of metabolic diseases with hyperglycemic characteristics that occur due to abnormal insulin secretion, insulin action or both. In managing the disease, the patient's role is very important, especially in terms of increasing adherence in establishing therapy in order to achieve optimal blood glucose levels to prevent more severe complications. Objective The relationship between patient characteristics and the level of adherence to lifestyle modification in the recovery of patients after DM Method This research is analytical research with cross sectional approach. This research was conducted in the Pelni Hospital Room in Jakarta in May 2017. The population was all patients with diabetes mellitus who came to the Pelni Hospital room. Sampling using a consecutive sampling technique with a total sample of 65 people. Primary data collection instruments using DM risk factor questionnaire. Results of the study In this study respondents who were the subject of the study were Diabetes Mellitus sufferers who visited the Pelni Hospital Inpatient Room Jakarta. Differences in characteristics possessed by each patient, can indirectly affect patient compliance in taking drugs. In table 1 it can be seen that in the age group below 45 years have a higher compliance that is equal to 70.0% compared to the age group above 45 years which is 25.5%. This shows the tendency between patient compliance in taking diabetes medications, where the younger the patient's age, the more likely it is to be obedient in consuming diabetes medications. Conclusion Based on the results of the study it can be concluded that there is a significant relationship between the age and level of education of patients with the level of adherence in undergoing treatment. However, there is no significant relationship between the sex of the patient and the level of adherence in undergoing treatment.